Specials - Westerfeld, Scott; Rosamilia, Mike; Simon Pulse; Simon and Schuster, inc. (New York : Simon Pulse, 2011)
When she is turned into a super-modelesque super-fighting machine, Tally, a former ugly, is ordered to keep the uglies down and the pretties stupid in a carefully engineered world of perfection where she refuses to play by the rules.
Reprint. Originally published: c2006.
Sequel to: Pretties.
"Simon Pulse an imprint of Simon & Shuster Children's Publishing Division ; Manufactured in the United States of America ; Book design by Mike Rosamilia"--t.p. verso.
Keywords: Beauty, Personal -- Juvenile fiction; Brainwashing -- Juvenile fiction; Technology -- Juvenile fiction; Fame -- Juvenile fiction; Dystopias -- Juvenile fiction; Ugliness -- Juvenile fiction; Teenage girls -- Juvenile fiction; Conformity -- Juvenile fiction; Popularity -- Juvenile fiction